Debt repayment practices among rural farmers: An Islamic economic perspective - Jannah, Maulidatul; Rusdiana, Rusdiana; Aisyah, Lisda (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2023)
This study focuses on the practice of debt repayment with rice in Martadah Village, Tambang Ulang District, Tanah Laut Regency, where the majority of the population are rice farmers. The primary aim of this study is to examine this practice from an Islamic economic perspective. The research employs a qualitative descriptive method involving observations, interviews, and documentation analysis related to the debt repayment practices in the village. The findings reveal that the debt repayment with rice often does not align with the qarḍ principles in Islamic economics, as the price of rice set by lenders is lower than the market price, causing losses to the farmers. The study also identifies the farmers’ dependency on capital owners and local community leaders, creating power dynamics and potential exploitation. Some cases show fairer practices consistent with qarḍ principles, where debt repayment is done at market prices without interest or additional profits. This study provides practical and theoretical contributions by emphasizing the importance of education and the application of Islamic economic principles to ensure fairness and social welfare in rural communities.